Eksplorasi Pola Bermain Game Online Mobile Legends: Bang Bang dan Dampaknya terhadap Pembentukan Karakter Islami Siswa Kelas IX MTs Nurul Huda Sumur Wangi Kota Bogor - Mohammad Bahrul Ilmi Thamrin; Bahrum Subagiya; Reni Sinta Dewi (Lembaga Yasin AlSys, 2025)
This study is motivated by the increasing intensity of online gaming among adolescents, particularly Mobile Legends: Bang Bang, which potentially influences the development of students' Islamic character. The objective of this research is to analyze the intensity and patterns of online gaming and to identify its impact on the formation of Islamic character among ninth-grade students at MTs. Nurul Huda Sumur Wangi, Bogor City, while also exploring the roles of teachers, parents, and the surrounding environment in reinforcing students’ Islamic values. A descriptive qualitative approach was employed, conducted from July to August 2025, with primary data obtained from interviews and observations, and secondary data drawn from documents and supporting publications. Data collection techniques included in-depth interviews, participatory observation, and documentation, while data validity was ensured through source and method triangulation. The findings reveal that students exhibit relatively high gaming intensity, playing 2–3 hours per day with a frequency of 10–20 sessions per week. This habit negatively affects Islamic character development, particularly in areas such as discipline in worship, sense of responsibility, emotional regulation, and ethical language use. These results underscore the crucial role of teachers, parents, and the environment in guiding and directing students to balance digital activities with Islamic values. The study concludes that a contextualized religious education strategy aligned with digital phenomena is essential as both a preventive and curative measure to mitigate the adverse effects of online gaming on students’ character development.